The Origins of Black Humanism in America - Floyd-Thomas, J. author. aut Link
XIV, 268 p.
Keywords: By examining the minister who helped inspire the founding of the Harlem Unitarian Church Reverend Ethelred Brown, Floyd-Thomas offers a provocative examination of the religious and intellectual roots of Black humanist thought.